(untitled) (Signifiances (Signifying), 2024)
This work will deal with the sign networks that are established between language and world in the work of semiotic different arts (poetry, music and architecture). The objective is to understand and analyze from Enaction theory and from the Semiotic sign of Peirce how the constant flow and ebb between social environment, body and language configure both language and the world. It will also be shown how the work of art constitutes an emergency in which language, body and social environment participate. To achieve these objectives, poetic texts by the Valencian author Ausiàs March and artistic works related to them will be analyzed. The work methodology includes sign analysis, the comparison of original texts with translations and the comparison of works of art of semiotic different kinds.